Metabolic changes in schizophrenia and human brain evolution - Philipp Khaitovich; Helen Lockstone; Matthew T. Wayland; Tsz M. Tsang; Samantha D Jayatilaka; Arfu J Guo; Jie Zhou; Mehmet Somel; Laura W. Harris; Elaine Holmes; Svante Pääbo; Sabine Bahn (2008)
Abstract Background Despite decades of research, the molecular changes responsible for the evolution of human cognitive abilities remain unknown. Comparative evolutionary studies provide detailed information about DNA sequence and mRNA expression differences between humans and other primates but, in the absence of other information, it has proved very difficult to identify molecular pathways relevant to human cognition. Results Here, we compare changes in gene expression and metabolite concentrations in the human brain and compare them to the changes seen in a disorder known to affect human cognitive abilities, schizophrenia. We find that both genes and metabolites relating to energy metabolism and energy-expensive brain functions are altered in schizophrenia and, at the same time, appear to have changed rapidly during recent human evolution, probably as a result of positive selection. Conclusion Our findings, along with several previous studies, suggest that the evolution of human cognitive abilities was accompanied by adaptive changes in brain metabolism, potentially pushing the human brain to the limit of its metabolic capabilities.